Current trends in Industry 4.0 and the supply chain in the period 2020 to 2023: A systematic review of the literature - Isaí Rojas Sánchez, David (2024)
This study examines the constantly evolving complexity of markets and the need for adaptation in supply chain management, highlighting the relevance of Industry 4.0. Through a systematic literature review of 40 articles published between 2020 and 2023, it analyzes the trends and crucial elements that connect both variables, discovering their strong link with three fundamental factors: sustainability, the actors involved and, finally, digitalization. Moreover, this study offers an original theoretical perspective on the current management of supply chain management, providing a referential framework that may be useful for future research in the field, while at the same time proposing a bibliographic methodological tool useful to the field of knowledge for its scrutiny through future research.